Re-framing Planning Decision-Making: Increasing Flood Resilience in Jakarta. Issue 3 (20th August 2014) - Sunarharum, Tri Mulyani; Sloan, Mellini; Susilawati, Connie
Abstract : Purpose: Rapid urbanisation, fragmented governance and recurrent flooding complicates resolution of DKI Jakarta's chronic housing shortage. Failure to effectively implement planning decision-making processes poses potential human rights violations. Contemporary planning policy requires the relocation of households living in floodplains within fifteen metres of DKI Jakarta's main watercourses; further constraining land availability and potentially requiring increased densification. The purpose of this paper is to re-frame planning decision-making to address risks of flooding and to increase community resilience. Design/methodology/approach: This paper presents a preliminary scoping study for a technologically enhanced participatory planning method, incorporating synthesis of existing information on urbanisation, governance, and flood risk management in Jakarta. Findings: Responsibility for flood risk management in DKI Jakarta is fragmented both within and across administrative boundaries. Decision-making is further complicated by: limited availability of land use data; uncertainty as to the delineated extent of watercourses, floodplains, and flood modelling; unclear risk and liability for infrastructure investments; and technical literacy of both public and government participants. Practical implications: This research provides information to facilitate consultation with government entities tasked with re-framing planning processes to increase public participation. Originality/value: This paper synthesises information from a range of sources not available in English, and offers insights into a complex system of governance and modes for improving decision-making.